Beginning Transact-SQL with SQL Server 2000 and 2005 - Turley, Paul, 1962- (Wrox beginning guides., 2006)
Beginning Transact-SQL with SQL Server 2000 and 2005 Transact-SQL is a powerful implementation of the ANSI standard SQL database query language. In order to build effective database applications, you must gain a thorough understanding of these features. This book provides you with a comprehensive introduction to the T-SQL language and shows you how it can be used to work with both the SQL Server 2000 and 2005 releases. Beginning with an overview of the SQL Server query operations and tools that are used with T-SQL, the author goes on to explain how to design and build applications o.